Archives of criminology and forensic sciences and scientific heritage of m. S. Bokarius - Fesiunіn Valentyn; Tiapkіn Anatolii (Archives of Criminology and Forensic Sciences, 2020)
Registration of new print media at National Scientific Centre «Hon. Prof. M. S. Bokarius Forensic Science Institute» is not accidental. Existing publications of the Ministry of Justice of Ukraine: Official Bulletin of Ukraine, Bulletin of the Ministry of Justice of Ukraine, the official collection: Systematic Collection of Current Legislation of Ukraine, the official periodical Codes of Ukraine, Theory and practice of Forensic science and Criminalistics by National Scientific Centre «Hon. Prof. M. S. Bokarius Forensic Science Institute», Criminalistics and Forensics by Kyiv Scientific Research Institute of Forensic Expertise, Interdepartmental scientific and methodological collection of the State Scientific Research Forensic Center (SSRFC) of the Ministry of Internal Affairs of Ukraine and professional scientific and practical collection: Kryminalistychnyi visnyk “concise” purpose, aspect. The system clearly lacks a periodical with regular headings and which contains official publications on public, scientific, industrial and other issues, literary and artistic works, essays, illustrations, advertising, interviews, the historical heritage of the M. S. Bokarius, famous scientist and etc. According to the State Register, there are more than 12,000 certified forensic experts in the country. The position of a forensic expert is by its nature exceptional, as it has certain features. On the one hand, the work of the expert is to conduct with the use of their specific expertise (almost unlimited range of issues: science, technology, crafts, etc.) a scientifically sound study to establish the facts that have probative value in the investigation and trial of cases with another hand, a forensic expert acquires the status of a procedural person in the provision of the conclusion and thus in his professional activity combines the status of a specialist in the relevant field of knowledge, scientist and procedural subject. The purpose of the article is to carry out a scientific search for new research papers of the scientist and to study five issues of the Archives of Criminology and Forensic Sciences published in 1926-1927.